Ziehl-Neelsen stain: a dated but useful tool for diagnosis of EPTB in resource-constrained settings - Datta, Sangeeta; Kumar, Avinash; Chatterjee, Biswaroop (International Journal of Research in Medical Sciences, 2024)
Background: Tuberculosis is one of the leading causes of mortality worldwide. The increasing prevalence of extrapulmonary tuberculosis (EPTB) is a cause of concern and its diagnosis still poses a major challenge to health care facilities. Methods: This was a retrospective study, covering a one-year period, at a tertiary-care hospital in Eastern India. The EPTB smear samples were subjected to Ziehl-Neelsen (Z-N) stain and examined. Also, fine needle aspiration cytology (FNAC) was performed on lesions at suitable sites. Results: Based on Z-N stain, EPTB was diagnosed in 40 out of 222 suspected cases (18.02%). The highest positivity was observed between 25 to 40 years (45%). The sex ratio was 2:1. Overall, the highest positivity was seen among pus samples (57.14%); followed by bronchoalveolar lavage fluid (40%), and aspirates from FNAC (14.3%, all of which had corroborating cytopathological features). Other samples, constituting of cerebrospinal fluid, synovial fluid, pleural fluid, ascitic fluid, urine and tissue were all negative by Z-N stain. Conclusion: Technological advances are being developed for faster and specific diagnosis of tuberculosis. However, conventional staining method and microscopic findings still remain useful, especially in resource-limited settings.